Biomimetic mineralization of diatom exoskeleton for sustainable pH-sensitive colored chitosan/silica hybrid self-supported films - Sandra Castanié; Laurent Billon (Materials & Design)
A gentle bio-inspired approach to the biosilicification occurring in diatom frustule is proposed to develop, at room temperature and without addition of a co-solvent, self-supported hybrid organic/inorganic films with pH-sensitive properties. It was found that chitosan (CS) biopolymer, a polysaccharide possessing numerous amine groups (–NH2) is capable of mimicking the action of the silaffins proteins of diatom frustule in the polycondensation process of the TetraEthoxyOrthoSilicate (TEOS) silica precursor to form a cohesive self-supported hybrid film under soft conditions in aqueous media. Thanks to its good film-forming property, hybrid chitosan/silica (CS/SiO2) films have been elaborated varying the amount of TEOS to study their optical and mechanical properties. It is shown that increasing the amount of TEOS up to 90 wt% improves the transparency, strength and stability of the films due to the interpenetration of the chitosan and silicaq networks. The incorporation of sustainable pH-sensitive alizarin dye during the elaboration of the films does not affect their mechanical properties whatever the composition. Moreover, these colored hybrid materials show good pH-sensitiveness under basic environment. Therefore, thanks to their antimicrobial properties and their pH-sensitivity, such self-supported films could be designed for applications such as smart sustainable food packaging and food degradation indicator.